Retroperitoneal haematoma causing gastric outflow obstruction following endovascular repair of a ruptured abdominal aortic aneurysm. (16th November 2012) - Hunter, Benjamin; Tod, Laura; Ghosh, Jonathan
Abstract : A 74-year-old man presented with back pain and collapse. A ruptured infrarenal abdominal aortic aneurysm was successfully managed by endovascular aneurysm repair. Postoperatively, he developed gastric outlet obstruction owing to duodenal compression from the unevacuated retroperitoneal haematoma. In the absence of abdominal compartment syndrome, conservative management with gastric decompression and parenteral nutrition led to a full recovery.